Media Background of Directors and Financial Risk Disclosure: Evidence from Indonesia - Mujtaba, Muhammad Irsyad Elfin; Aini, Siti Nur; Narsa, I Made (Accounting Analysis Journal, 2024)
Purpose: This research aims to examine the impact of the media background of board members on the financial risk disclosure practices of companies in the Indonesian business context. Method: The research method utilized data from non-financial companies listed on the Indonesia Stock Exchange (IDX) during the period 2010-2021. Ordinary Least Squares (OLS) regression analysis was employed to test the relationship between the independent variable (media background of board members) and the dependent variable (the quality of financial risk disclosure). Findings: The results of the study indicate that board members with a media background tend to disclose fewer financial risks, suggesting that the influence of a media background can affect financial risk disclosure practices. Novelty: The novelty of this research lies in exploring the impact of media backgrounds in the context of financial risk disclosure in Indonesian companies, providing new insights into the dynamics of corporate governance and the role of media in an increasingly information-driven era.